Pengaruh Penyaluran Kredit dan Kredit Macet Terhadap Perputaran Arus Kas Pada Koperasi Serba Usaha (KSU) Se-Kecamatan Tegallalang Gianyar - Ni Putu Karniasih; Ni Komang Sumadi; Ni Putu Trisna Windika Pratiwi (UNHI Press, 2026)
ABSTRACT Cash flow turnover is an important indicator in assessing the liquidity and operational efficiency of cooperatives. Cash flow reflects the extent to which a cooperative can generate cash from its business activities to meet short-term obligations, finance daily operations, and support business growth. This study aims to analyze the effect of loan disbursement and non-performing loans on cash flow turnover in Multipurpose Cooperatives (KSU) throughout Tegallalang District, Gianyar. This research uses a quantitative approach with secondary data obtained from the financial statements of 32 active cooperatives that served as research samples. Data analysis was carried out using IBM SPSS, with testing stages including the classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis, coefficient of determination test (Adjusted R²), simultaneous test (F-test), and partial test (t-test). The results show that (1) loan disbursement has a positive and significant effect on cash flow turnover, and (2) non-performing loans have a negative and significant effect on cash flow turnover. Based on these findings, it is recommended that cooperatives improve the effectiveness of loan disbursement and strengthen the non-performing loan control system to maintain cash flow stability and support the sustainability of cooperative operations.